2022
DOI: 10.1177/2752535x221133140
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 vaccination experience of non-English speaking immigrant and refugee communities of color: A community co-created study

Abstract: In this community-partnered study we conducted focus groups with non-English speaking immigrant and refugee communities of color in 4 languages to understand their perspectives on COVID-19 vaccines, barriers to accessing vaccines, and recommendations for healthcare providers. We used a mixed deductive-inductive thematic analysis approach and human centered design to guide data analysis. 66 individuals participated; 85% were vaccinated. The vaccination experience was often positive; however, participants descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Existing barriers to equitable care, including language barriers, economic insecurity, and a lack of convenient access to health facilities persisted during the pandemic and disproportionately impacted vulnerable groups including women, persons with disabilities, the unhoused, the elderly and refugee, immigrant and migrant (RIM) communities (Abba‐Aji et al, 2022; Berger et al, 2020). Likewise, mistrust of the government and a lack of cultural understanding on the part of government and health agencies also emerged as impediments to care for many (Baines et al, 2022; Gonzalez et al, 2020; Salib et al, 2022). These challenges can be broadly categorized into physical and attitudinal barriers (Fisk, 2021), both of which are further investigated in this study.…”
Section: Challenges and Barriers For Vulnerable Communities During Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…Existing barriers to equitable care, including language barriers, economic insecurity, and a lack of convenient access to health facilities persisted during the pandemic and disproportionately impacted vulnerable groups including women, persons with disabilities, the unhoused, the elderly and refugee, immigrant and migrant (RIM) communities (Abba‐Aji et al, 2022; Berger et al, 2020). Likewise, mistrust of the government and a lack of cultural understanding on the part of government and health agencies also emerged as impediments to care for many (Baines et al, 2022; Gonzalez et al, 2020; Salib et al, 2022). These challenges can be broadly categorized into physical and attitudinal barriers (Fisk, 2021), both of which are further investigated in this study.…”
Section: Challenges and Barriers For Vulnerable Communities During Co...mentioning
confidence: 99%
“…Among the barriers experienced by vulnerable communities, such as refugee and migrant communities, is a lack of language fluency (Baines et al, 2022; Bastick & Mallet‐Garcia, 2022; Gonzalez et al, 2020; Salib et al, 2022; Shaw et al, 2022). In addition to general language‐related struggles, newer arrivals with limited English language skills may struggle to understand nuanced or technical health‐related information made available by the media and health professionals alike, featuring either medical jargon or colloquial language (Baines et al, 2022; Bastick & Mallet‐Garcia, 2022; Salib et al, 2022; Shaw et al, 2022).…”
Section: Challenges and Barriers For Vulnerable Communities During Co...mentioning
confidence: 99%
“…In this regard, Ayash et al found that vaccination uptake among immigrant were more likely among those with higher education, with more years in the destination country, and with higher household income ( 7 ). In addition, community-based organizations played a role in connecting participants to vaccines ( 8 ).…”
Section: Dear Editor-in-chiefmentioning
confidence: 99%
“…Salib et al reported the vaccination experience was often positive among immigrants; however, they described language inaccessibility, often relying on family members for interpretation. Unvaccinated participants expressed fear of side effects and belief in natural immunity ( 8 ).…”
Section: Dear Editor-in-chiefmentioning
confidence: 99%
“…Throughout the COVID-19 pandemic, immigrant-focused CBOs have additionally played critical roles in increasing access to COVID-19 testing and vaccination for immigrant communities. 19 , 20 Given the role that DSPs often play for their immigrant clients, such as serving as trusted sources of information, intermediaries, or care navigators, they are well situated to discuss the mechanisms by which the pandemic, and its associated health care and public health policies, has impacted existing disparities for pregnant immigrant people. Critically, we felt this approach allowed us to gather information that might be challenging or uncomfortable for immigrant people to disclose themselves, due to immigration status-related fears or the inherent power imbalances that might be felt by immigrant research participants.…”
Section: Introductionmentioning
confidence: 99%